2014
DOI: 10.1016/j.marpetgeo.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of dolomitizing fluids and Mg source evaluation of fault-controlled dolomitization at the Benicàssim outcrop analogue (Maestrat basin, E Spain)

Abstract: The mechanisms responsible for the formation of huge volumes of dolomitized rocks associated with faults are not well understood. We present a case study for high-temperature dolomitization of an Early Cretaceous (Aptian-Albian) ramp in Benicàssim (Maestrat basin, E Spain). In this area, seismic-scale fault-controlled stratabound dolostone bodies extend over several kilometres away from large-scale faults. This work aims at evaluating different Mg sources for dolomitization, estimating the reactivity of dolomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 83 publications
(135 reference statements)
3
56
0
Order By: Relevance
“…The Benassal Fm is partially dolomitized in close association with the aforementioned regional faults, constituting a world-class case study of fault-controlled dolomitization and associated Mississippi Valley-Type (MVT) mineralization recently reported in the literature (Martín-Martín et al 2013Corbella et al 2014;Gomez-Rivas et al 2014b). These previous studies reported dolostone bodies of tens of meters thick that extend several km away from seismic-scale faults with a dominant stratabound distribution.…”
Section: Fault-controlled Dolostonesmentioning
confidence: 93%
See 1 more Smart Citation
“…The Benassal Fm is partially dolomitized in close association with the aforementioned regional faults, constituting a world-class case study of fault-controlled dolomitization and associated Mississippi Valley-Type (MVT) mineralization recently reported in the literature (Martín-Martín et al 2013Corbella et al 2014;Gomez-Rivas et al 2014b). These previous studies reported dolostone bodies of tens of meters thick that extend several km away from seismic-scale faults with a dominant stratabound distribution.…”
Section: Fault-controlled Dolostonesmentioning
confidence: 93%
“…This paper reports the role of stylolites in the burial dolomitization and subsequent hydrothermal corrosion that affects the Benassal Fm (Late Aptian-early Albian) platform carbonates located in Benicàssim (Maestrat Basin, E Spain). Previous works dealing with the dolostones of the Benicàssim area focused on the study of the replacement process (Martín-Martín et al 2013;Corbella et al 2014;Gomez-Rivas et al 2014b;Martín-Martín et al 2015), and concentrated on well-exposed stratabound dolostones cropping out in areas relatively far away from the seismic-scale faults that acted as feeders for dolomitizing fluids. However, the areas closer to the fault zones are not equally well documented, although these represent areas of high interest.…”
mentioning
confidence: 99%
“…Although truly quantitative predictions using RTM are still difficult to achieve (e.g. Katz et al 2011), compare and contrast studies allow us to link depositional environments and climate variations to patterns of early diagenesis (Whitaker & Xiao 2010;Whitaker et al 2014) or to quantify how strata and structures around three-dimensional (3D) faults influence resulting patterns of dolomite geobody characteristics Gomez-Rivas et al 2014). The outcome of RTM models can then guide the modelling of geobodies, porosity and permeability evolution in between wells, ensuring that the static geological model is self-consistent.…”
Section: Selected Advancesmentioning
confidence: 99%
“…The application of RTM to fault systems in 3D remains limited but is critical to understanding the ways by which the combined impacts of strata and structures influence the resulting patterns of dolomite geobody characteristics. A few 3D studies have provided insights into the rock types and structural associations that strongly influence reservoir quality trends around faults Gomez-Rivas et al 2014) (Fig. 8).…”
Section: Fundamental Controls On Fluid Flow In Carbonatesmentioning
confidence: 99%
See 1 more Smart Citation